A pH-triggered self-releasing humic acid hydrogel loaded with porcine interferon α/γ achieves anti-pseudorabies virus effects by oral administration - Maoyuan Sun; Yongli Shi; Baishi Lei; Wuchao Zhang; Jingjing Feng; Shenghu Ge; Wanzhe Yuan; Kuan Zhao (Veterinary Research)
Abstract Interferon α (IFNα) and interferon γ (IFNγ) play pivotal roles in mediating crucial biological functions, including antiviral activity and immune regulation. However, the efficacy of monomeric IFN is limited, and its administration relies solely on injection. To address this issue, we successfully expressed and purified a recombinant porcine IFNα and IFNγ fusion protein (rPoIFNα/γ). Furthermore, we developed a pH-triggered humic acid hydrogel delivery system that effectively protects rPoIFNα/γ from gastric acid degradation, enhancing its oral bioavailability. Neither the humic acid hydrogel nor rPoIFNα/γ exhibited cytotoxic effects on porcine kidney-15 (PK-15) cells in vitro. The replication of vesicular stomatitis virus and pseudorabies virus (PRV) was effectively inhibited by rPoIFNα/γ, resulting in an antiviral activity of approximately 104 U/mL. Scanning electron microscopy revealed that the humic acid hydrogel had a loose and porous honeycomb structure. The IFNα/γ@PAMgel hydrogel effectively adsorbed rPoIFNα/γ, as confirmed by Fourier transform infrared spectroscopy analysis, demonstrating a favourable IFN-loading capacity. In vitro experiments revealed that IFNα/γ@PAMgel swelled and released IFNα/γ rapidly at pH 7.4 but not at pH 1.2. The oral administration of IFNα/γ@PAMgel in mice enhanced the proliferation and differentiation of CD4+ and CD8+ cells. Additionally, mice infected with PRV and treated with IFNα/γ@PAMgel presented increased transcription levels of interferon-stimulated genes in the serum, reduced mortality rates, lower viral loads in various tissues, and decreased levels of organ damage. In conclusion, this study demonstrates that orally administered IFNα/γ@PAMgel has antiviral and immunomodulatory effects, highlighting its potential as a therapeutic agent against PRV infection.